2009
DOI: 10.1080/01446190903002797
|View full text |Cite
|
Sign up to set email alerts
|

Defects in offsite construction: timber module prefabrication

Abstract: The construction industry is based on craftsmanship. Quality control and assurance procedures applied in manufacturing cannot usually be readily applied in construction, where there are higher degrees of uniqueness in each project. One category of companies, industrialized housebuilders, is attempting to bridge some of the gaps between construction and manufacturing. These companies prefabricate building modules for later assembly at the building site. Since they are wholly responsible for large parts of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 15 publications
0
51
0
Order By: Relevance
“…This research has shown the root causes of the defects were structural design error and bad craftsmanship. Much of the defects occurred during the 2-year warranty period, with almost half of these originating from factory production where during a factory audit structural design contributed to $30% of defects (Johnsson and Meiling, 2009). The structural design defects identified are a movement of the structure, severe cracking to the corners as well as the misplacement of openings and poor material choice by the architect and structural engineer.…”
Section: Municipal Engineer Volume 170 Issue Me4mentioning
confidence: 99%
See 1 more Smart Citation
“…This research has shown the root causes of the defects were structural design error and bad craftsmanship. Much of the defects occurred during the 2-year warranty period, with almost half of these originating from factory production where during a factory audit structural design contributed to $30% of defects (Johnsson and Meiling, 2009). The structural design defects identified are a movement of the structure, severe cracking to the corners as well as the misplacement of openings and poor material choice by the architect and structural engineer.…”
Section: Municipal Engineer Volume 170 Issue Me4mentioning
confidence: 99%
“…The structural design defects identified are a movement of the structure, severe cracking to the corners as well as the misplacement of openings and poor material choice by the architect and structural engineer. As a critical response to the research by Johnsson and Meiling (2009), several interesting issues were identified, notably whether these defects were the result of poor technical detailing (impregnation, surface coatings and seasoning) rather than purely engineering design factors.…”
Section: Municipal Engineer Volume 170 Issue Me4mentioning
confidence: 99%
“…In contrast to previous research that emphasizes that modularization always aims to gain benefits in the construction phase, related to improved cost efficiency, quality or schedule (Gibb 1999, Haas et al 2000, Pasquire and Gibb 2002, Pan et al 2008, Johnsson and Meiling 2009, Isaac et al 2016, our framework highlights that in addition to those objectives, modularization can aim at innovative design solutions if project stakeholders' knowledge assets (Robertson and Ulrich 1998) related to modularization are used when designing repetitive spaces or structures, and they are connected to a fabricate-to-order strategy (Ulrich 1995). At the other…”
Section: Strategies To Adopt Modular Product Architecturementioning
confidence: 78%
“…Therefore, before considering the adoption of modularization in the building investment, the crucial question is as follows: What is the problem that modularization is aiming to solve? The earlier research focus on modularization in construction may not always have been completely sharp in terms of providing new knowledge about specific outcomes, such as quality improvement through modular construction (Johnsson and Meiling 2009), design configuration utilizing industrialized platforms (Wikberg et al 2014) and implications for maintenance costs (Pan et al 2007), among others. These studies provide practitioners with useful knowledge about how to utilize modularization and similar concepts in specific settings and specific parts of the construction supply chain, but they do not extensively describe the variety of modularization strategies.…”
Section: Modular Product Architecture and Product Platformsmentioning
confidence: 99%
See 1 more Smart Citation